PENGARUH PENGGUNAAN MEDIA BONEKA TANGAN TERHADAP KEMAMPUAN MENYIMAK PADA ANAK USIA 5-6 TAHUN KELOMPOK B2 DI TK KRISTEN CITRA BANGSA MANDIRI KUPANG - Yosefa Bakhita Mano; G. Betty, Credo; Nama Koten, Angelikus; Margiani, Kristin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Listening skill is one of the important aspects of early childhood language development. Based on preliminary observations at TK Kristen Citra Bangsa Mandiri Kupang, the listening ability of children aged 5–6 years had not developed optimally. This study aimed to determine the effect of using hand puppet media on the listening ability of children aged 5–6 years at TK Kristen Citra Bangsa Mandiri Kupang. This research employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest Design. The sample consisted of 10 children selected through purposive sampling. Data were collected through observation and documentation. The data were analyzed using the Paired Sample t-test. The results showed that the use of hand puppet media had a significant effect on children's listening ability. This was indicated by an increase in the mean score from 12.3 in the pretest to 17.9 in the posttest, with a significance value of 0.000 < 0.05. Therefore, it can be concluded that the use of hand puppet media significantly improves the listening ability of children aged 5–6 years. Hand puppet media can attract children's attention, helping them focus, understand instructions, answer questions, and retell information received during the learning process.